A preliminary analysis of the DDC 780 class (music) in the 20th edition - Pegoraro Novaes, Fernanda Carolina [UNESP]; Moreira, Walter [UNESP]; Santana De Moraes, Isabela [UNESP] (My University, 2019)
The general objective of this study is to demonstrate the importance and the impact that the modifications made in the DDC’s 20th edition brought to the music class. For this purpose, the titles of the first level subsections (.1-.9) of division 780 in DDC issues 18, 19 and 20 were analyzed. The methodology chosen for this study was a multi-faceted ontogeny analysis. As a result, it is possible to affirm that the editorial exchange carried out to broaden the cultural context in the DDC, were relevant for the conceptual revision and the breaking of biases previously verified in the music class. The analysis demonstrated how a classification scheme can not solve problems generated by a specific domain alone, necessitating the addition of other forms of organization (as discussed in division 780). The organization and treatment of documents in music is still under development in the area of Librarianship and Information Science, so this research can contribute to provide theoretical assumptions and other perspectives to future works.
Ontogenia da divisão 780 (música) na classificação decimal de dewey: Uma análise preliminar da 20ª edição
Keywords: Bibliographic classification; DDC 20th edition; Dewey decimal classification; Music; Ontogeny